Model Halaqah Reflektif Berbasis Nilai Karakter Keislaman Untuk Penguatan Lifelong Learning dalam Pembelajaran Pendidikan Agama Islam - Niswatin Abdul Cholik; Nangkula Utaberta (TARBAWI : Jurnal Pendidikan Agama Islam, 2026)
Islamic Religious Education (IRE) learning in senior high schools has not yet systematically fostered a lifelong learning (LLL) orientation, despite the fact that Islamic values such as thalab al-ʿilm (the pursuit of knowledge), muhasabah (self-reflection), and istiqamah (steadfastness) have the potential to serve as its foundation. This study aims to analyze: (1) the current condition of IRE learning in fostering lifelong learning orientation among high school students; (2) the development process of the Reflective Halaqah Model based on Islamic character values; and (3) indications of improvements in students’ lifelong learning orientation following the implementation of the model. The study employed a Design-Based Research (DBR) approach using qualitative and descriptive quantitative data. Data were collected through in-depth interviews, classroom observations, document analysis, and perception surveys involving six IRE teachers, 34 students, and three experts from public senior high schools in Depok. The findings indicate that the Reflective Halaqah Model, validated through a Content Validity Index (CVI = 0.92), is content-valid and demonstrates indications of improvement across all lifelong learning indicators, with the highest increase observed in lifelong learning orientation (+0.94 points on a 1–5 scale). This study introduces the construct of faith-based lifelong learning, which operationalizes Islamic values as the foundation for self-regulation and autonomous motivation in IRE learning, while also responding to the demands of the Merdeka Curriculum and the Pancasila Student Profile. Keywords: lifelong learning, Islamic character values, Islamic Religious Education, Reflective Halaqah Model, Design-Based Research.